Cognitive and Physiologic Impacts of the Infraslow Oscillation - Watson, Brendon O. (Frontiers in Systems Neuroscience, 2018)
Brain states are traditionally recognized via sleep-wake cycles, but modern neuroscience is beginning to identify many sub-states within these larger arousal types. Multiple lines of converging evidence now point to the infraslow oscillation as a mediator of brain sub-states, with impacts ranging from the creation of resting state networks in awake subjects to interruptions in neural activity during sleep. This review will explore first the basic characteristics of the infraslow oscillation in human subjects before reviewing findings in sleep and in animals. Networks of consistently correlated brain regions known as resting state networks seen in human functional neuroimaging studies oscillate together at infraslow frequencies. The infraslow rhythm subdivides nonREM in a manner that may correlate with plasticity. The mechanism of this oscillation may be found in the thalamus and may ultimately come from glial cells. Finally, I review the functional impacts of infraslow oscillations on brain phenomena ranging from higher frequency oscillations, to brain networks, to information representation and cognitive performance. Infraslow oscillations represent a relatively understudied phenomenon with wide effects on the brain and behavior.